CONSERVATIVE VERSUS RADICAL TREATMENT OF ASCENDING AORTIC DILATION: COMPARATIVE ANALYSIS OF BASELINE CLINICAL DATA FOLLOWING WRAPPING, NO-TOUCH SURGICAL AORTIC VALVE REPLACEMENT, AND THE WHEAT PROCEDURE - Zelenchuk, Oleh; Nechai, Illia; Mokryk, Igor; Stetsyuk, Ihor; Demyanchuk, Vitaly; Todurov, Borys (Eastern Ukrainian Medical Journal, 2026)
Background: The optimal management of ascending aortic dilation in patients undergoing aortic valve replacement (AVR) remains debated. Although replacement of the ascending aorta is widely considered the standard, conservative strategies such as wrapping are still used in selected patients.Objective: This study aimed to analyze baseline characteristics and etiological patterns in patients treated with wrapping, supracoronary replacement (Wheat procedure), or isolated AVR without intervention on the ascending aorta.Methods: This retrospective, single-center analysis included 120 patients who underwent AVR in the presence of ascending aortic dilation (>40 mm) between 2016 and 2024. Patients with connective tissue disorders, prior aortic surgery, or acute aortic syndromes were excluded. After propensity score matching, 40 patients were assigned to each group: AVR with wrapping, Wheat procedure, and no-touch AVR. Demographic, clinical, and echocardiographic data were compared to identify factors associated with aortic dilation.Results: Patients in the No-touch group were significantly older (69.5 ± 5.2 years) compared with the Wheat (51.2 ± 13.7 years) and Wrapping (50.4 ± 13.3 years) groups (p < 0.001). Bicuspid valve morphology predominated in the Wheat (72.5%) and Wrapping (62.5%) groups, while tricuspid valves were most frequent in the No-touch group (80%; p < 0.001). Ascending aortic diameters were larger in the Wheat and Wrapping groups compared with No-touch (p < 0.001). The No-touch cohort showed more advanced ventricular remodeling, higher rates of left ventricular dilation, reduced ejection fraction, and increased pulmonary pressures. Neurological events and preoperative atrial fibrillation were also more common.Conclusion: Distinct etiological profiles exist among patients with ascending aortic dilation undergoing AVR. Wrapping and replacement were used mainly in younger patients with bicuspid valves and larger diameters, whereas the no-touch strategy was applied in older patients with tricuspid valves and ventricular dysfunction. These findings support individualized treatment based on valve phenotype, age, and etiology.